Globally mobile middle class lives in government secondary schools. Issue 5 (3rd September 2019) - Higginson, Joanne; McLeod, Julie; Rizvi, Fazal
ABSTRACT: Schooling has long been studied for its role in class formation and reproduction, Australian government secondary schools have also traditionally been associated with 'the local' and with 'nation building'. Some schools might now also be engaged with ideas of the 'the global' not only through policy practices and priorities, but also through the social dynamics of migration and movement. In globalizing times neither class formation nor schooling can be thought of simply in national terms. They are connected to globalizing forces yet cannot be divorced from their national specificity. We suggest that within Australia recent and historical emphases on skilled migration are pivotal to considering local connections to global middle class circuits. We argue for new approaches to studying the school experiences of global middle-class families and students, through a focus on transnational connectivities, generational dynamics, family and social life, rather than on more 'culturalist' approaches and national comparisons.